Isolation of Nuclei from Mammalian Cells and Tissues for Single‐Nucleus Molecular Profiling. Issue 5 (27th May 2021) - Nadelmann, Emily R.; Gorham, Joshua M.; Reichart, Daniel; Delaughter, Daniel M.; Wakimoto, Hiroko; Lindberg, Eric L.; Litviňukova, Monika; Maatz, Henrike; Curran, Justin J.; Ischiu Gutierrez, Daniela; Hübner, Norbert; Seidman, Christine E.; et al.
Abstract: Both single‐cell RNA sequencing (scRNAseq) and single‐nucleus RNA sequencing (snRNAseq) can be used to characterize the transcriptional profile of individual cells, and based on these transcriptional profiles, help define cell type distribution in mixed cell populations. However, scRNAseq analyses are confounded if some of the cells are large (>50 µm) or if some of cells adhere more tightly to some adjacent cells than to others. Further, single cell isolation for scRNAseq requires fresh tissue, which may not be available for human or animal model tissues. Additionally, the current enzymatic and mechanical methods for single‐cell dissociation can lead to stress‐induced transcriptional artifacts. Nuclei for snRNAseq, on the other hand, can be isolated from any cell, regardless of size, and from either fresh or frozen tissues, and compared to whole cells, they are more resistant to mechanical pressures and appear not to exhibit as many cell isolation‐based transcriptional artifacts. Here, we describe a time‐ and cost‐effective procedure to isolate nuclei from mammalian cells and tissues. The protocol incorporates steps to mechanically disrupt samples to release nuclei. Compared to conventional nuclei isolation protocols, the approach described here increases overall efficiency, eliminates risk of contaminant exposure, and reduces volumes of expensive reagents. A series of RNA quality control checks are also incorporated to ensure success and reduce costs of subsequent snRNAseq experiments. Nuclei isolated by this procedure can be separated on the 10× Genomics Chromium system for either snRNAseq and/or Single‐Nucleus ATAC‐Seq (snATAC‐Seq), and is also compatible with other single cell platforms. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Sample preparation and quality control check via RNA Isolation and Analysis Basic Protocol 2 : Nuclei Isolation